The Role of Green Economy Legal Instruments in Advancing Sustainable Development - Indah Dwiprigitaningtias; Lily Andayani; Andi Ajeng (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study aims to examine the role of green economy legal instruments in advancing sustainable development and to analyze how these instruments function within contemporary environmental governance systems. The study also explores the contribution of legal mechanisms to environmental accountability, ecological justice, and sustainability transitions. Design/methodology/approach – This research employs a normative legal research design using statutory, conceptual, and analytical approaches. The analysis is based on primary, secondary, and tertiary legal materials, including environmental regulations, international policy frameworks, academic literature, and institutional reports. The collected materials were analyzed through qualitative legal analysis to identify the preventive, corrective, and transformative functions of green economy legal instruments. Finding/Results – The findings reveal that green economy legal instruments operate through three interconnected functions. Preventive instruments reduce environmental risks through environmental impact assessments, permitting systems, environmental standards, and spatial planning regulations. Corrective instruments strengthen environmental accountability through sanctions, liability mechanisms, compensation schemes, and ecological restoration measures. Transformative instruments facilitate sustainability transitions by promoting renewable energy development, green investment, innovation, and resource-efficient economic practices. The study further finds that the effectiveness of these instruments depends on regulatory coherence, institutional capacity, enforcement effectiveness, and meaningful public participation. Originality/Value – This study contributes to the literature by proposing an integrated framework that conceptualizes green economy legal instruments as preventive, corrective, and transformative mechanisms operating simultaneously within environmental governance systems. The framework enriches discussions on environmental law, ecological justice, and sustainable development while providing practical insights for strengthening sustainability-oriented legal governance.